Analysis and Simulation of the Mechanical Property of Transmission Steel Belt - Zhang Haifeng; Wu Jiwei; Yu Jiali; Chen Ting; Zeng Qi; Yang Yicheng (Jixie chuandong, 2017)
In order to meet the requirements of strength and service life of steel belt in the transmission process,the mechanical property of the transmission steel belt is analyzed,and comes to the conclusion that the main reasons for the changes of the steel belt stress are the initial tension,the thickness of the steel belt,roller diameter,and finds out where the maximum stress may occur. At the same time,based on theory,the kinetic and dynamic characteristics of steel belt are analyzed. Finally,by using the Recur Dyn software,steel belt is stimulated,the relevant dynamics and kinematics curves are got and compared with the theoretical analysis,a reference for the design and calculation of steel belt is provided.